Mouse H-2(k)-restricted cytotoxic T cells recognize antigenic determinants in both the HA1 and HA2 subunits of the influenza A/PR/8/34 hemagglutinin - Gould, K; Scotney, H; Townsend, A; Bastin, J; Brownlee, G (1987)
We have constructed two chimeric influenza hemagglutinin (HA) genes in which the HA1 and HA2 subunits of the HA molecule have been interchanged between influenza A/PR/8/34 (H1 subtype) and A/NT/60/68 (H3 subtype). These genes were used to construct recombinant vaccinia viruses that expressed intact chimeric HA. These recombinant viruses were used to test whether murine CTL recognize antigenic determinants in either the HA1, HA2, or both subunits. We found that both subunits of the HA molecule contain determinants for CTL. This implies that CTL have, at least in part, separate antigenic determinants from B lymphocytes, which recognize mainly epitopes within the HA1 subunit.